2014
DOI: 10.1007/s00266-014-0387-2
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine-Induced ASC Apoptosis (Tumescent vs. Local Anesthesia)

Abstract: Tumescent anesthesia is the superior method for liposuction with respect to ASC preservation compared to local anesthesia. Lidocaine could cause significant ASC apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…12,13 Because patients often undergo general anesthesia, lidocaine subcutaneous anesthesia seems unnecessary because lidocaine could compromise SVF and ASC survival in the lipoaspirate. 18,26,27 For example, in our previous study, 18 we have reported that lidocaine has significant and a negative impact on ASC survival in the lipoaspirate that is used for fat grafting. Girard et al 26 reported that lidocaine has a negative impact on ASCs even when the ASCs were exposed for only 1 or 2 hours.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12,13 Because patients often undergo general anesthesia, lidocaine subcutaneous anesthesia seems unnecessary because lidocaine could compromise SVF and ASC survival in the lipoaspirate. 18,26,27 For example, in our previous study, 18 we have reported that lidocaine has significant and a negative impact on ASC survival in the lipoaspirate that is used for fat grafting. Girard et al 26 reported that lidocaine has a negative impact on ASCs even when the ASCs were exposed for only 1 or 2 hours.…”
Section: Discussionmentioning
confidence: 99%
“…18,2225 Our prior preliminary data based on 7 subjects indicate that the difference in the response of matched pairs is normally distributed with SD 386.7 and the difference between means is 514.3. If the true difference of ASC number in the mean response of matched pairs is 514.3, we will need to study 6 to 8 pairs of subjects to be able to reject the null hypothesis that this response difference is 0 with probability (power) 0.9 (90%).…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations